Is Vaginal Breech Delivery Still a Safe Option? - Maria Pulido Valente; Maria Carvalho Afonso; Nuno Clode (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2020)
Abstract Objective: To determine whether there was any difference in neonatal and maternal outcomes between breech vaginal delivery and cephalic vaginal delivery. Methods: A retrospective, case-control study was conducted between January 2015 and December 2017 in a Portuguese hospital. A total of 26 cases of breech vaginal delivery were considered eligible and 52 pregnant women formed the control group. Results: Induced labor was more frequent in the breech vaginal delivery group (46% versus 21%, p = 0.022). Episiotomy was more common in the breech vaginal delivery group (80% versus 52%, p = 0.014), and one woman had a 3rd degree perineal laceration. Newborns in the study group had a lower birthweight (2,805 g versus 3,177 g, p < 0.001). There was no significant difference in the neonatal outcomes. Conclusion: The present study showed that breech vaginal delivery at term compared with cephalic presentation was not associated with significant differences in neonatal and maternal morbidity. It also suggests that breech vaginal delivery remains a safe option under strict selection criteria and in the presence of an experienced obstetrician.